Conformational Heterogeneity and Quasi-Static Self-Quenching in DNA Containing a Fluorescent Guanine Analogue, 3MI or 6MI - Wojtuszewski Poulin, Kristi; Smirnov, Aleksandr V; Hawkins, Mary E; Balis, Frank M; Knutson, Jay R (Biochemistry (Easton), 2009)
Two different microenvironments in the DNA sequence 5′-act aGa gat ccc tca gac cct ttt agt cag tGt gga-3′ (in both single- and double-stranded forms) are explored using two similar fluorescent nucleoside analogues, 3MI and 6MI. Each probe was evaluated in two environments, one strand with the probe flanked by thymines (PTRT) and the other by adenines (PTRA) with positions indicated by G’s in the sequence. Both time-resolved anisotropies and lifetimes of the probes depend upon local interactions, and these are altered by duplex formation. Integrals of lifetime curves compared with quantum yields reveal that each probe displays a “dark” component (below detection limits, with a lifetime of <70 ps). For 6MI in PTRA, this QSSQ “quasi-static self-quenching” or “dark” component represents approximately half the molecules, whether in single- or double-stranded form. In PTRT, 6MI displays an unusual increase in the quantum yield upon formation of the double strand (from 0.107 to 0.189) apparently the result of escape from QSSQ which simultaneously declines from 66 to 33%. This is also accompanied by doubling of steady-state anisotropy. Only 6MI in the PTRT duplex displays a rotational correlation time of >7 ns. In other words, the DS 6MI PTRA environment fails to constrain local motion and QSSQ remains the same as in the single strand; in contrast, the flanking T duplex environment restricts local motion and halves QSSQ. We collected both steady-state and time-resolved fluorescence quenching titrations of 3MI and 6MI in solution with the mononucleotides AMP, CMP, GMP, and TMP. The dynamic quenching rank of the free probes (quenching constant, k q: T > A > G > C) is totally different from that of incorporated probes. We hypothesize the production of weak 3MI·C or 6MI·C complexes that are somehow rendered less subject to dynamic quenching by collision with subsequent C molecules.